Treatment Strategies for Infections With Shiga Toxin-Producing Escherichia coli - Mühlen, Sabrina; Dersch, Petra (Frontiers in Cellular and Infection Microbiology, 2020)
Infections with Shiga toxin-producing Escherichia coli (STEC) cause outbreaks of severe diarrheal disease in children and the elderly around the world. The severe complications associated with toxin production and release range from bloody diarrhea and hemorrhagic colitis to hemolytic-uremic syndrome, kidney failure and neurological issues. As the use of antibiotics for treatment of the infection has long been controversial due to reports that antibiotics may increase the production of Shiga toxin, the recommended therapy today is mainly supportive. In recent years, a variety of alternative treatment approaches such as monoclonal antibodies or antisera directed against Shiga toxin, toxin receptor analogues and several vaccination strategies have been developed and evaluated in vitro and in animal models. A few strategies have progressed to the clinical trial phase. Here, we review the current understanding of and the progress made in the development of treatment options against STEC infections and discuss their potential.